Propofol inhibits stromatoxin-1-sensitive voltage-dependent K+ channels in pancreatic β-cells and enhances insulin secretion - Kusunoki,Munenori; Hayashi,Mikio; Shoji,Tomohiro; Uba,Takeo; Tanaka,Hiromasa; Sumi,Chisato; Matsuo,Yoshiyuki; Hirota,Kiichi (PeerJ, 2019)
Background Proper glycemic control is an important goal of critical care medicine, including perioperative patient care that can influence patients’ prognosis. Insulin secretion from pancreatic β-cells is generally assumed to play a critical role in glycemic control in response to an elevated blood glucose concentration. Many animal and human studies have demonstrated that perioperative drugs, including volatile anesthetics, have an impact on glucose-stimulated insulin secretion (GSIS). However, the effects of the intravenous anesthetic propofol on glucose metabolism and insulin sensitivity are largely unknown at present. Methods The effect of propofol on insulin secretion under low glucose or high glucose was examined in mouse MIN6 cells, rat INS-1 cells, and mouse pancreatic β-cells/islets. Cellular oxygen or energy metabolism was measured by Extracellular Flux Analyzer. Expression of glucose transporter 2 (GLUT2), potassium channels, and insulin mRNA was assessed by qRT-PCR. Protein expression of voltage-dependent potassium channels (Kv2) was also assessed by immunoblot. Propofol’s effects on potassium channels including stromatoxin-1-sensitive Kv channels and cellular oxygen and energy metabolisms were also examined. Results We showed that propofol, at clinically relevant doses, facilitates insulin secretion under low glucose conditions and GSIS in MIN6, INS-1 cells, and pancreatic β-cells/islets. Propofol did not affect intracellular ATP or ADP concentrations and cellular oxygen or energy metabolism. The mRNA expression of GLUT2 and channels including the voltage-dependent calcium channels Cav1.2, Kir6.2, and SUR1 subunit of KATP, and Kv2 were not affected by glucose or propofol. Finally, we demonstrated that propofol specifically blocks Kv currents in β-cells, resulting in insulin secretion in the presence of glucose. Conclusions Our data support the hypothesis that glucose induces membrane depolarization at the distal site, leading to KATP channel closure, and that the closure of Kv channels by propofol depolarization in β-cells enhances Ca2+ entry, leading to insulin secretion. Because its activity is dependent on GSIS, propofol and its derivatives are potential compounds that enhance and initiate β-cell electrical activity.
Keywords: Insulin; Pancreatic β-cells; Propofol; Kv channel; Stromatoxin-1; Anesthetic; Glucose